Valuation of Lost Productivity in Caregivers: A Validation Study - Gelfand, Aaron; Sou, Julie; Sawatzky, Rick; Prescott, Katrina; Pearce, Alison; Anis, Aslam H.; Lee, Christine; Zhang, Wei (Frontiers in Psychology, 2021)
Objective: This study aimed to: a) adapt the previously validated Valuation of Lost Productivity (VOLP) questionnaire for people with health problems, to a caregiver version to measure productivity losses associated with caregiving responsibilities, and b) evaluate measurement feasibility and validity of an online version of the caregiver VOLP questionnaire. Methods: A mixed methods design was utilized. Qualitative methods, such as reviewing existing questionnaires that measured caregiver work productivity losses and performing one-on-one interviews with caregivers, were used for VOLP adaptation and online conversion. Quantitative methods were used to evaluate feasibility and validity of the online VOLP. The Work Productivity and Activity Impairment (WPAI) questionnaire for caregivers was included to compare its absenteeism and presenteeism outcomes and their correlations with VOLP outcomes. Results: When adapting the VOLP for caregivers, our qualitative analysis showed the importance of adding three major components: caregiving time, work productivity loss related to volunteer activities and caregivers’ lost job opportunities. A total of 383 caregivers who completed online survey were included in our final quantitative analysis. We found small Spearman rank correlations between VOLP and WPAI, observing a larger correlation between their absenteeism (r = 0.49 (95% confidence interval: 0.37-0.60)) than their presenteeism (r = 0.36 (0.24-0.47)). Correlations between VOLP outcomes and total caregiving hours were larger for absenteeism (r = 0.38 (0.27-0.47)) than presenteeism (r = 0.22 (0.10-0.34)). Correlations between WPAI outcomes and total caregiving hours were smaller for absenteeism (r = 0.27 (0.15-0.38)) than presenteeism (r = 0.35 (0.23-0.46)). Conclusion: The study provides evidence of the feasibility and preliminary validity evidence of the adapted VOLP caregiver questionnaire in measuring productivity losses due to caregiving responsibilities, when compared with the results for WPAI and the results from the previous patient-VOLP validation study.